PSYCHO-NEUROLOGICAL FEATURES OF NEUROSES IN CHILDREN - Ozodova Diana Sardor kizi; Saidkhodjaeva S.N.; Nurkhodjaev S.N. (Galaxy International Interdisciplinary Research Journal, 2024)
This article delves into the intricate psycho-neurological features of neuroses in children, exploring the various manifestations, underlying causes, and potential interventions. Through a comprehensive literature analysis, the study investigates the methods used in diagnosing and treating childhood neuroses, followed by a discussion on the results and implications for further research. Ultimately, this article aims to enhance our understanding of neuroses in children and provide insights into effective therapeutic approaches.